Pengembangan sekolah SDN 4 Rarang melalui In House Training media pembelajaran - Baiq Desi Dwi Arianti; Baiq Mahyatun; Maman Asrobi (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2022)
The Indonesian government is promoting 21st Century learning by implementing HOTS (High Order Thinking Skill) and TPACK (Technological, Pedagogical, Content Knowledge). The implementation of this system has felt the impact when there has been a Covid 19 pandemic since 2020. This situation has forced the entire learning process to change. All learning is required through online learning. Teachers and students have difficulty adjusting because they cannot use technology in the learning process. SDN 4 Rarang has teachers who are mainly able to master essential technology but do not take advantage of this ability to develop learning media. Therefore, this activity aims to train teachers at SDN 4 Rarang in developing learning media in the form of learning videos and uploading these videos to the YouTube page. The method used is lecture and practice. The participants of the activity were 9 teachers. The results of this activity are from 9 teachers who participated in the training, 7 people have been able to make learning videos and upload the videos to the YouTube page, while 2 people still do not master the material because one of them is age factor, so that the acceptance of training materials is not conveyed correctly. Good, with an achievement percentage of 83.9%.